Rapid Reactivation of Open Coil Springs: A Novel Approach (Orthodontic Journal of Nepal, 2015)
A fast and simple technique for rapid reactivation of open coil springs using prefabricated self cure acrylic discs has been demostrated. Arch wire removal is not required in this technique and varying levels of reactivation are possible depending upon the clinical situation.